2011
DOI: 10.2337/dc11-1026
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Prevalence of Diabetic Ketoacidosis at Diagnosis of Type 1 Diabetes in Young Children Participating in Longitudinal Follow-Up

Abstract: OBJECTIVEYoung children have an unacceptably high prevalence of diabetic ketoacidosis (DKA) at the clinical diagnosis of type 1 diabetes. The aim of this study was to determine whether knowledge of genetic risk and close follow-up for development of islet autoantibodies through participation in The Environmental Determinants of Diabetes in the Young (TEDDY) study results in lower prevalence of DKA at diabetes onset in children aged <2 and <5 years compared with population-based incidence studies and registries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 148 publications
(137 citation statements)
references
References 21 publications
5
124
2
6
Order By: Relevance
“…15 The Environmental Determinants of Diabetes in the Young (TEDDY) Study recently found that DKA prevalence in youth ,5 years of age who were followed regularly and educated about diabetes in the TEDDY study was lower than among registry youth who were not under follow-up, suggesting that parental education, closer monitoring of signs and symptoms of diabetes, and knowledge of being at high risk of type 1 diabetes can result in lower DKA prevalence at onset of diabetes. 30 Finally, our findings of a higher prevalence of DKA in minority youth with type 1 diabetes, youth without private insurance, and those with lower family income are consistent with previous US reports 31 and suggest a persistent need for improved health care access.…”
Section: Type 2 Diabetessupporting
confidence: 81%
“…15 The Environmental Determinants of Diabetes in the Young (TEDDY) Study recently found that DKA prevalence in youth ,5 years of age who were followed regularly and educated about diabetes in the TEDDY study was lower than among registry youth who were not under follow-up, suggesting that parental education, closer monitoring of signs and symptoms of diabetes, and knowledge of being at high risk of type 1 diabetes can result in lower DKA prevalence at onset of diabetes. 30 Finally, our findings of a higher prevalence of DKA in minority youth with type 1 diabetes, youth without private insurance, and those with lower family income are consistent with previous US reports 31 and suggest a persistent need for improved health care access.…”
Section: Type 2 Diabetessupporting
confidence: 81%
“…The frequency of DKA in children with a family history of diabetes was somewhat lower than in the TEDDY (The Environmental Determinants of Diabetes in the Young) Study (8.8% vs 11.3%) [19], although the TEDDY Study only comprised patients under the age of five, who were The model with IDAA 1c as outcome variable was not applicable due to infinite likelihood. We combined the groups of CSII duration from 3 months to 2 years, and the estimates are illustrated accordingly intensely followed before and after the time of diagnosis [19].…”
Section: Discussionmentioning
confidence: 99%
“…These populationbased surveys represent countries with a high annual background incidence of type 1 diabetes comparable with that of Denmark [18]. Elding Larsson et al, who followed-up and screened children genetically at risk of diabetes for diabetesspecific autoantibodies in a multinational study, found that participation in the study was associated with reduced risk of DKA [19]. However, despite prevention campaigns and an improved system of medical care [20,21], the rate of DKA remains unacceptably high.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Although research indicates that intensive diabetes management reduces the risk of acute and chronic complications of type 1 diabetes, medical expenditures for its complications remain substantial. [4][5][6] Short-term complications from type 1 diabetes represent one of the most potentially preventable causes of hospitalization in children, accounting for $67 million in hospital costs per year. 7 Health care reform efforts in the United States emphasize identification of areas in which better patient outcomes and lower costs intersect, especially in children and adults with chronic diseases associated with preventable complications.…”
mentioning
confidence: 99%